Analysis of Differences in the Function Groups of Bioactive Compounds of Noni and Papaya Leaf Extracts as Antibacterial Agents Using FTIR Spectrophotometer - Al-Hakiim, R. M. Pradikalisatryo Rizqiravendra; Maulidyah, Putri; Andiarna, Funsu; Agustina, Eva; Purnamasari, Risa; Lusiana, Nova; Hidayati, Irul (International Conference on Sustainable Health Promotion, 2025)
Noni (Morinda citrifolia) and papaya (Carica papaya) are plants that are abundant in Indonesia and have traditionally been used as medicine. This study aims to analyze the differences in functional groups of noni and papaya leaf extracts as antibacterial agents. The extracts were obtained through maceration using 96% ethanol as the solvent. Fourier Transform Infrared Spectroscopy (FTIR) was used in this study to identify the functional groups of bioactive compounds in each extract. The FTIR spectrum of noni leaves showed the presence of alkaloid functional groups due to the characteristic absorption of the -NH functional group of alkaloids at a wavelength of 3335.96736 cm-1, while papaya leaves showed the presence of saponin functional groups due to the characteristic absorption of the -OH functional group of saponins at 3337.83103 cm-1. Both compounds exhibit broad biological activity, including as antibacterial agents. Alkaloids from noni leaves have been proven effective against Staphylococcus aureus bacteria (causing acne), while saponins from papaya leaves are effective against Escherichia coli (the cause of diarrhea). Extracts from noni and papaya leaves show significant potential as natural antibacterial agents, supported by the identification of alkaloid and saponin functional groups through FTIR analysis.